Application of TiO2 Nanotube As Photoelectrode For Corrosion Prevention Of Stainless Steel In pH Variation of NaCl - Misriyani, Misriyani; Wahab, Abdul Wahid; Taba, Paulina; Gunlazuardi, Jarnuzi (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2015)
The research amis to synthesize TiO2 nanotube photoelectrode (TiO2-NT) by anodizing method. The photoelectrodes applied in photoelectrochemical system to prevent the corrosion of steel. Anodizing method carried out by preparing an electrochemical system consisting of a titanium plate as anode and Pt wire as cathode in electrolyte containing glycerol, ammonium fluoride and water. Voltage applied from the DC current source and followed by thermal treatment at a temperature of 500oC. The photoelectrode further characterized by using X-Ray Diffraction and Surface Area Analyzer. The result of anti-corrosion test of stainless steel 304 by TiO2-NT showed that photopotential value of steel shifted to the more negative value in UV light. The significant potential shift occurs at pH 8 and the corrosion rate of stainless steel 304 couple with TiO2-NT decrease reaches 1.7 times. It concluded that the photoelectrodes can be used to reduce the corrosion rate of stainless steel 304 by utilizing sollar energy as a source of UV light.